Dynamic Interactions between Large-Scale Brain Networks Predict Behavioral Adaptation after Perceptual Errors - Cohen, Michael X (Oxford University Press, 2013)
Failures to perceive visual stimuli lead to errors in decision making. Different theoretical accounts implicate either medial frontal (MF) cognitive control processes or prestimulus occipital (OC) cortical oscillatory dynamics in errors during perceptual tasks. Here, we show that these 2 previously unconnected theoretical accounts can be reconciled, and the brain regions described by the 2 theories have complimentary and interactive roles in supporting error adaptation. Using a perceptual discrimination task and time–frequency network-based analyses of electroencephalography data, we show that perceptual anticipation and posterror top–down control mechanisms recruit distinct but interacting brain networks. MF sites were a hub for theta-band networks and theta–alpha coupling elicited after errors, whereas occipital sites were a network hub during stimulus anticipation and alpha–gamma coupling. Granger causality analyses revealed that these networks communicate in their preferred direction and frequency band: response-related MF → OC interactions occurred in the theta band, whereas stimulus anticipation-related OC → MF interactions occurred in the alpha band. Subjects with stronger network interactions were more likely to improve performance after errors. These findings demonstrate that multiple large-scale brain networks interact dynamically and in a directionally specific manner in different frequency bands to support flexible behavior adaptation during perceptual decision making.